من (النَّصّ) إلى (النَّصّ المفتوح) في الخطاب النقديّ العربيّ المعاصر - برهم لطفيّة; عطية قصي (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
ينشد هذا البحث تقديم رؤية واضحة لمفهوم (النَّصّ) في الدراسات النقديَّة، التي أفادت من النّظريَّات الغربيَّة، وخاصّة المتَّصلة بتاريخ الأدب وتحليل النّصوص الأدبيَّة، وانتقاله إلى مرحلة جديدة، هي (النَّصّ المفتوح)، و(التّفاعل النصّيّ) واتّساع دائرته؛ لتشمل العلامات غير اللسانيَّة، فالنَّصّ لا يتفاعل مع نصوصٍ شفاهيَّة أو مكتوبة فحسب، وإنّما يتفاعل أيضاً مع نصوصٍ من أنظمة علامات أخرى غير لسانيَّة تفاعلاً يتجاوز النَّصّ، في بعده اللفظيّ، إلى نصوصٍ ذات طبيعة صوريَّة أو صوتيَّة. ومع التطوُّر العلميّ وثورة المعلومات والاتّصالات، فرضت التكنولوجيا الحديثة (النّصّ الإلكترونيّ أو الرقميّ)، الذي يحيل على دور الوسيط (الحاسوب) في تقديم النَّصّ والتواصل معه، من خلال شاشة الحاسوب. The aim of this article is to give a clear view of the concept of (the text) in the critical studies, that profit from western theories, especially those connected with the history of literature, and analyzing literary texts, and its moving into a new stage. It is (the open text) and (the text interaction) and text enlargement; to contain the features of the in langoustine, so the text doesn’t interact only with oral or written texts, but it interacts, also, with texts from systems of different features in langoustine, interaction pass the text in its pronunciation into texts have a picturesque nature, or vocal. And with the development of science, information revolution, and communication, the new technology forced (the electronic text or digital) that return into agent turn (the computer) in introducing the text, and communicating with it, through the computer screen.